Perceived Abusive Leadership, Narcissistic Personality, and Employee's Political Behaviors: A Moderated-Mediation Model. (November 2022) - Lin, Chen-Ju; Pauleen, David; Li, Ci-Rong
Limited research has explored the potential explanatory mechanisms for the link between abusive leadership and non-negative employee-based behaviors in the effectiveness of organizational management. Based on affective response theory to construct a theoretical model, this study enhances the mapping of how employee-perceived abusive leadership triggers employee affective responses and influences their political behaviors to facilitate task-related goals. It also investigates how the moderating effects of employee-perceived leader's narcissistic personality interact with the variables of the main effects. This study was implemented in Taiwan's financial and insurance institutions. Using a sampling framework via a market survey agency, participants completed three online surveys within a 3-week period. 350 employed participants registered for the study. Based on the findings, we suggest that managers in a hierarchical organization may be able to intentionally vary their leadership style to arouse employees' negative emotions without hindering, and perhaps even improving, employees' motivation to achieve their task aims. When leaders demonstrate their self-confidence in the workplace, employees perceive less anxiety at work and less need to adopt workplace political behaviors to solve work troubles. This research suggests managers should recognize employee-perceived abusive leadership as an influential factor that contributes to illuminating the processes underlying workplace perception-to-behavior and leader–member interactive links, as well as the boundary conditions of mediating and moderating these processes.